Begin with the past : building the National Museum of African American History & Culture - Wilson, Mabel O.; Bunch, Lonnie G. (Washington, DC : Smithsonian Books, 2016)
"The Building of the National Museum of African American History and Culture traces the making of this unparalleled museum. Founding director Lonnie G. Bunch III described it as "ten years in the making, and 100 years in the making," and Mabel O. Wilson explores that effort in her narrative. As she discovers, initial calls for a permanent place to collect, study, and present African American history and culture in the early twentieth century never got off the ground. In the late 1990s, the notion began to gain momentum from increasing public interest and Congressional support. In 2003 the museum was officially established. Yet the work of the museum was only just beginning. Wilson takes an in-depth look at the selection of the director, site, and architects in the years that followed. Rising on the National Mall next to the Washington Monument, the museum is a tiered bronze beacon inviting us to understand our past and embrace our future. Wilson explores how the "four pillars" of the museum's mission shaped its powerful structure, and she teases out the rich cultural symbols and homages layered into the design of the building and its surrounding landscape. This book is an important inside look at the making of a monument"
Includes index.
boek
Keywords: Freelon Adjaye Bond/SmithGroup.; National Museum of African American History and Culture (U.S.).; Museum architecture -- Washington (D.C.).; Washington (D.C.) -- Buildings, structures, etc